2007
DOI: 10.1161/strokeaha.106.478362
|View full text |Cite
|
Sign up to set email alerts
|

Serum Glial Fibrillary Acidic Protein Is Related to Focal Brain Injury and Outcome After Aneurysmal Subarachnoid Hemorrhage

Abstract: Background and Purpose— Aneurysmal subarachnoid hemorrhage (aSAH) stands out from other subtypes of stroke because of the high early mortality and the risk of complications. Serum glial fibrillary acidic protein (s-GFAP) concentrations are increased after stroke. The aim of this study was to investigate whether s-GFAP could be used as a marker of brain damage and outcome after aSAH. Methods— Serum samples were ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 19 publications
1
54
0
Order By: Relevance
“…During a 2-week period after SAH, higher s-GFAP levels in the patient groups with radiological signs of focal lesions and patients with secondary events were observed. Their results indicate that s-GFAP provides information about injury severity and outcome after SAH and demonstrate its potential to refl ect the brain damage [81] .…”
Section: Proteinmentioning
confidence: 93%
“…During a 2-week period after SAH, higher s-GFAP levels in the patient groups with radiological signs of focal lesions and patients with secondary events were observed. Their results indicate that s-GFAP provides information about injury severity and outcome after SAH and demonstrate its potential to refl ect the brain damage [81] .…”
Section: Proteinmentioning
confidence: 93%
“…Possible candidates include glial fibrillary-associated protein and brain-and heart-type fatty acid binding protein. Glial fibrillary-associated protein levels are related to severity of injury and adverse outcomes after traumatic brain injury [107], and to neurological outcome after stroke [108] and subarachnoid haemorrhage [109]. Brain-and heart-type fatty acid binding protein show higher sensitivities and specificities than protein S100B and neuron specific enolase in the rapid detection of brain injury in stroke, trauma and neurodegenerative diseases [110].…”
Section: The Futurementioning
confidence: 99%
“…Moreover, any increase in the level of serum GFAP can depend on the magnitude of brain damage and its duration. It was observed that serum GFAP level was increased in different neurological diseases with characteristic persistent and chronic brain damage, including multiple sclerosis, glioblastoma, Parkinson disease, traumatic brain injury, and subarachnoid haemorrhage [13][14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%